Realizing Farmer's Objectives - Imperative to Adoption Process of Fish Farming Technology - Saha, Biswarup (Indian Journal of Extension Education, 2015)
This study was conducted to investigate how realizing farmer's perception as well as objective has an influence on the  adoption process of fish farming technology in Tripura. An ex- post facto research design was employed to collect data  from 200 respondents randomly sampled from 10 villages. Instruments used for data collection included semi structured  interview schedule, Participatory Rural Appraisal, researchers' observations and secondary information sources. The  overall adoption index in the study area was found 59.74. Farmers who realized their objective intensified the activity and  were able to produce 412 kg/kani (1kani=2.5 Acre/0.16ha) production that was considered more profitable than other crop  production. Those who did not realize their objectives abandoned or practiced low level technology. This finding  suggested that farmer's objective and priority should be known before introduction of the technology and efforts should be  directed towards realizing the objectives. Additionally, efforts should be made to improve production technology,  preparation and preservation skills and harvest strategies.
Keywords: Fish farmers; perception; technology; adoption gap